Surface enhanced CdSe/ZnS QD/SiNP electrochemical immunosensor for the detection of Mycobacterium tuberculosis by combination of CFP10-ESAT6 for better diagnostic specificity - Mohd Bakhori, Noremylia; Yusof, Nor Azah; Abdullah, Jaafar; Wasoh @ Mohamad Isa, Helmi; Ab. Rahman, Siti Khadijah; Abd Rahman, Siti Fatimah (MDPI, 2020)
In this study, an electrochemical immunosensor was introduced for the detection of tuberculosis (TB) via utilization of a modified electrode containing a quantum dot (CdSe/ZnS QD) and functionalized silica nanoparticles (SiNPs) on screen-printed carbon electrode (SPCE) CdSe/ZnS QD/SiNPs/SPCE, by employing indirect enzyme-linked immunosorbent assay (ELISA). Here, the fabricated electrode was linked to the biocatalytic action of enzyme catalase through antigen–antibody binding for the detection of the antigen (CFP10–ESAT6) by means of producing a differential pulse voltammetry (DPV) current. The characterization and cyclic voltammetry (CV) of the modified electrode showed good electrochemical behavior and enhanced high electron transfer between the electrode and analyte. Moreover, the active surface area was 4.14-fold higher than the bare SPCE. The developed method showed high selectivity towards CFP10–ESAT6 compared with the other TB proteins. The detection of CFP10–ESAT6 also showed a linear response towards different concentrations of CFP10–ESAT6 with R2 = 0.9937, yielding a limit of detection (LOD) of as low as 1.5 × 10−10 g/mL for a linear range of 40 to 100 ng/mL of CFP10–ESAT6 concentration. The proposed method showed good reproducibility of target analyte with a relative standard deviation of 1.45%.